Thermal diffusion and diffusion thermo effects on axi-symmetric boundary layer flow of nanofluid due to non-linear stretching sheet along the radial direction in presence of magnetic field - Ganga, Upender Reddy; Janaiah, Ch.; Shankar Goud, B. (Zielona Góra: Uniwersytet Zielonogórski)
This work presents the results of numerical research that was conducted on the flow of axisymmetric nanofluids through a nonlinearly stretched sheet in the radial direction while a magnetic field influence was present. This model of a nanofluid demonstrates the presence of both the Brownian motion and the thermophoretic nanoparticle diffusion effects simultaneously. When calculating the flow, both the Dufour effect and the Soret effect are taken into consideration.
Keywords: thermal diffusion; nanofluid; axi-symmetric flow; non-linearly stretching sheet; Runge-Kutta method